Measuring the Quality of Student Support Services in Open Distance E-Learning - Aberra, Tsige, GebreMeskel (My University, 2020)
Student support services are essential elements in the success of open distance e-learning. These services help students to become competent in achieving their goals. However, the level of the quality of services should be measured so that continuous improvements can be made, which in turn bring about sustainability of positive results. This article takes content validity as its focus in the development of an instrument. By exposing the instrument to 10 experts, items were refined in the form of deletions, additions, and the splitting of double-barrelled items. Experts ratings were analysed through the content validity index for each item, each dimension and the overall instrument. The content validity processes undertaken in this article have resulted in getting a 50-item 5-dimensional instrument. The use of content validity procedures is one of the most recommended methods in securing the validity of an instrument in terms of its involving appropriate items and dimensions.
Keywords: content validity; student support; service quality; ODeL; Ethiopia